L’Asie orientale : Une option régionale pour le Canada? - Hervouet, Gérard (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1983)
No more than any other geographical region has East Asia ever really been a priority in the Canadian foreign policy. The rapid economic growth of this sub-continent has stirred Canadian interest in East Asia. This interest, expressed mainly in terms of the economy - commerce and investments - meets with numerous barriers, some specific to the region, others related to the constraints resulting from the international economic competition. In a y et more obvious way, the diplomacy of the government in Ottawa meets with internal obstacles particular to the Canadian society which, by tradition and inclination, usually has a tendency to turn more towards the Atlantic ocean. The objective of this study is therefore to identify those constraints while at the same time underlining the new efforts deployed by the Federal government to build up an increased interest in that region. This paper tries also to pinpoint the way in which the Asian policy is incapable of elaborating corrective measures to the problems still present to-day, but which have long been well indentified.